Method for preparing modified graphite fluoride nanosheet in one step by liquid phase stripping method and battery
Modified graphite fluorinated nanosheets were prepared by liquid phase peeling method, which solved the problems of poor rate performance and low voltage platform of lithium/fluorinated carbon batteries, and achieved improved conductivity and optimized battery performance.
Patent Information
- Application Number
- CN202510117662.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-25
AI Technical Summary
The lithium/carbon fluoride battery has poor rate performance and low voltage platform for large rate discharge during discharge, which limits its application.
Modified graphite nanosheets are prepared in one step by a liquid phase peeling method, which includes dispersing fluorinated carbons in anhydrous ethanol solution, adding deionized water and defluorinating agent, and carrying out hydrothermal reactions to achieve defluorination and oxygen doping of the fluorinated carbons.
It significantly improves the conductivity of carbon fluoride, ensures the high specific capacity of lithium/fluoride carbon batteries, and increases the platform voltage of the battery during large-scale discharge, significantly improving the electrochemical performance.
Smart Images

Figure CN119683619A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of carbon fluoride, and in particular to a preparation method of modified fluorinated graphite nanosheets and a battery. Background Art
[0002] Lithium / carbon fluoride batteries are lithium primary batteries with the highest theoretical energy density in the world. In addition, lithium / carbon fluoride batteries have the advantages of long life, low self-discharge, wide operating temperature range, and environmental friendliness. They have broad application prospects in the fields of electronic devices, biomedicine, and equipment power supplies, and have great market potential, attracting much attention from researchers. However, carbon fluoride itself has poor conductivity, which makes lithium / carbon fluoride batteries have poor rate performance during discharge and low voltage platform for high-rate discharge. These problems seriously restrict the application of lithium / carbon fluoride batteries.
[0003] Carbon monoxide (CO) has strong reducing properties and is often used to reduce compounds to generate the desired substances. For example, in the metallurgical industry, carbon monoxide is often used as a reducing agent to extract metals from metal oxides. In a high-temperature furnace, carbon monoxide can reduce iron ore (the main component is iron oxide (Fe2O3)) to generate metallic iron (Fe). The strong reducing property of carbon monoxide can also be used for reductive defluorination. During the reductive defluorination process, carbon monoxide reduces the fluorine atoms in fluorine-containing compounds to generate carbon dioxide (CO2) and hydrogen fluoride (HF). Taking the reduction of calcium fluoride (CaF2) by carbon monoxide as an example, its reductive defluorination reaction can be expressed as carbon monoxide reducing the fluorine in calcium fluoride to generate metallic calcium (Ca), carbon dioxide and hydrogen fluoride. Oxalic acid (H2C2O4) begins to decompose when heated to 189.5 degrees Celsius, and the decomposition products are carbon dioxide, carbon monoxide and water. The generated carbon dioxide can enter the gaps between the layered carbon fluoride layers and transform them into flaky graphite fluoride nanosheets. The generated carbon monoxide has strong reducing properties and can cause carbon fluoride to undergo a reduction reaction to reduce the fluorine content of the carbon fluoride. The defects generated during defluorination make it easier for oxygen to be incorporated into the material, thereby achieving synchronous oxygen doping. This allows carbon fluoride to achieve the effects of defluorination, heteroatom doping and functional group modification, which improves the electrical conductivity of carbon fluoride while ensuring the high specific capacity of the lithium / carbon fluoride battery and increasing the platform voltage of the lithium / carbon fluoride battery at high-rate discharge, significantly improving the electrochemical performance of the lithium / carbon fluoride battery. Summary of the invention
[0004] In view of this, the present invention provides a method for preparing modified fluorinated graphite nanosheets in one step by a liquid phase exfoliation method and a battery, which realizes oxygen doping while reducing the fluorine content of carbon fluoride, thereby obtaining a modified fluorinated graphite nanosheet with excellent electrochemical properties, which improves the electrical conductivity of carbon fluoride while ensuring the high specific capacity of the lithium / carbon fluoride battery and improving the platform voltage of the lithium / carbon fluoride battery during high-rate discharge, thereby significantly improving the electrochemical performance of the lithium / carbon fluoride battery.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] An embodiment of the present invention provides a method for preparing modified fluorinated graphite nanosheets, the method comprising:
[0007] The carbon fluoride is dispersed in an anhydrous ethanol solution, and then deionized water and a defluorinating agent are added to form a mixed solution, and then the mixed solution is stirred to completely dissolve the defluorinating agent, and the mixed solution containing the defluorinating agent is ultrasonically dispersed and then hydrothermally reacted at 100 to 300 degrees Celsius for 4 to 8 hours, and the product after the hydrothermal reaction is repeatedly washed with anhydrous ethanol and deionized water three times and then freeze-dried to obtain a modified fluorinated graphite nanosheet. The modified fluorinated graphite nanosheet has a fluorine content of 31% to 54% and an oxygen doping amount of 0.69% to 3.50%.
[0008] Wherein, the method further comprises:
[0009] (1) dispersing carbon fluoride in an anhydrous ethanol solution, stirring for 10 minutes and then ultrasonicating for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0010] (2) adding deionized water and a defluorinating agent to the dispersed carbon fluoride solution, wherein the mass ratio of carbon fluoride to the defluorinating agent is 1:(0.5-3.0), stirring for 10 minutes to fully dissolve the defluorinating agent, ultrasonicating for 10 minutes, and stirring for 30 minutes to make it evenly dispersed;
[0011] (3) subjecting the above-mentioned fully dispersed mixed solution to a hydrothermal reaction at 100 to 300 degrees Celsius for 4 to 8 hours, during which the defluorinating agent is thermally decomposed to produce carbon dioxide, carbon monoxide and water, wherein carbon monoxide has a strong reducing property and can cause the carbon fluoride to undergo a reduction defluorination reaction;
[0012] (4) washing the product of the hydrothermal reaction with deionized water and anhydrous ethanol alternately and repeatedly by suction filtration three times, and freeze-drying the sample after washing the residual solvent to obtain modified fluorinated graphite nanosheets;
[0013] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with a conductive agent, a binder, etc., an electrode is obtained for assembling a lithium / carbon fluoride battery.
[0014] The fluorine content of the carbon fluoride is 50-70%, and the oxygen content is 0-0.69%.
[0015] Wherein, the defluorination agent includes at least one of oxalic acid, sodium bicarbonate and carbon monoxide.
[0016] Wherein, the oxygen source includes at least one of oxalic acid and sodium bicarbonate.
[0017] During the hydrothermal reaction, oxalic acid is heated to decompose and produce carbon dioxide, carbon monoxide and water. The generated carbon dioxide can enter the gaps between the layered carbon fluoride layers and transform them into flaky graphite fluoride nanosheets. The generated carbon monoxide has strong reducing properties and can undergo a reduction reaction with fluorine in the carbon fluoride to achieve defluorination, generating carbon dioxide and hydrogen fluoride. The fluorine content of the carbon fluoride is significantly reduced after reductive defluorination, and oxygen is added to the material during the reaction, so that the oxygen content of the material is significantly higher than that of the original material.
[0018] The slurry adjustment ratio is a mass ratio of carbon fluoride: conductive agent: binder, including at least one of 8:1:1, 0.82:0.09:0.09 and 0.86:0.07:0.07.
[0019] Wherein, the conductive agent includes at least one of Ketjen black, Super P, carbon nanotubes and carbon fibers.
[0020] Wherein, the binder is at least one of polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0021] The slurry preparation solvent is N-methylpyrrolidone (NMP), and the modified fluorinated graphite nanosheets, the conductive agent, and the binder are made into a slurry, which is coated on a carbon-coated aluminum foil, and then cut into pieces after drying to prepare electrodes.
[0022] The present invention provides a method and a battery for preparing modified fluorinated graphite nanosheets in one step by a liquid phase exfoliation method, wherein carbon fluoride is fully dispersed in a mixture of deionized water and anhydrous ethanol, a defluorinating agent is added, and a hydrothermal reaction is carried out at 100 to 300 degrees Celsius for 4 to 8 hours. The product after the hydrothermal reaction is repeatedly washed three times with anhydrous ethanol and deionized water and then freeze-dried to obtain a modified fluorinated graphite nanosheet; wherein, due to the different masses of the added defluorinating agent, the obtained modified fluorinated graphite nanosheets have different fluorine contents (31% to 54%) and different oxygen doping amounts (0.69% to 3.50%); by The defluorinating agent reduces the fluorine content of carbon fluoride, and utilizes the defects generated in the defluorination process to provide a large number of oxygen atom embedding sites, thereby successfully achieving oxygen doping; in the defluorination process, a large number of CF bonds of carbon fluoride are broken to expose carbon atoms on the surface of carbon fluoride, wherein the exposed carbon provides a good conductive network, which can significantly improve the conductivity of carbon fluoride, and also ensure the high specific capacity of lithium / carbon fluoride batteries and improve the platform voltage of lithium / carbon fluoride batteries during high-rate discharge; at the same time, the modified fluorinated graphite nanosheets in the present invention have good conductivity and superior rate performance, laying a foundation for the application of lithium / carbon fluoride batteries in the high-power field.
[0023] Compared with the prior art, it has the following beneficial effects:
[0024] 1. Oxalic acid and carbon fluoride were used to achieve controllable defluorination and preparation of oxygen-doped fluorinated graphite nanosheets in one step through a hydrothermal method;
[0025] 2. In the hydrothermal reaction, oxalic acid is decomposed by heat to generate carbon dioxide, carbon monoxide and water. Carbon dioxide can enter the gaps between the layers of layered carbon fluoride and transform it into flaky graphite fluoride nanosheets. The strong reducing property of carbon monoxide can react with the fluorine in carbon fluoride to achieve defluorination, significantly reducing the fluorine content of carbon fluoride while exposing carbon atoms on the surface of carbon fluoride, thereby improving the conductivity of carbon fluoride.
[0026] 3. After defluorination, the defects of carbon fluoride increase, and oxygen is more easily doped into carbon fluoride, realizing the synchronous doping of oxygen in carbon fluoride, greatly increasing the relative contents of C=C, CO and C=O in carbon fluoride, improving the conductivity of carbon fluoride and also improving the transmission efficiency of electrons and ions during discharge of lithium / carbon fluoride battery, ensuring the high specific capacity of lithium / carbon fluoride battery and improving the platform voltage of lithium / carbon fluoride battery at high rate discharge, significantly improving the electrochemical performance of lithium / carbon fluoride battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of carbon fluoride and modified graphite fluoride nanosheets provided in one embodiment of the present invention;
[0028] Figure 2 C1s spectra of carbon fluoride and modified fluorinated graphite nanosheets provided in one embodiment of the present invention;
[0029] Figure 3 A constant current discharge diagram of a lithium / carbon fluoride battery equipped with carbon fluoride and modified graphite fluoride nanosheets as positive electrode active materials at a discharge rate of 8C provided in one embodiment of the present invention;
[0030] Figure 4 This is a constant current discharge diagram of a lithium / carbon fluoride battery equipped with modified fluorinated graphite nanosheets as positive electrode active materials at a discharge rate of 45C provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] Embodiment 1
[0033] In this embodiment, a modified fluorinated graphite nanosheet with a fluorine content of 46.43% and an oxygen content of 2.28% is prepared by taking fluorinated carbon with a fluorine content of 55.97% as a raw material as an example, and the effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified by specific experiments, as follows:
[0034] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0035] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.5 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.5, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0036] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of the reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 200 degrees Celsius for 6 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0037] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0038] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0039] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0040] Embodiment 2
[0041] In this embodiment, a modified fluorinated graphite nanosheet with a fluorine content of 52.00% and an oxygen content of 1.20% is prepared by taking fluorinated carbon with a fluorine content of 55.97% as a raw material as an example, and the effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified by specific experiments, as follows:
[0042] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0043] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 0.9 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:0.9, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0044] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of the reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 200 degrees Celsius for 6 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0045] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0046] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0047] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0048] Embodiment 3
[0049] In this embodiment, a modified fluorinated graphite nanosheet with a fluorine content of 50.00% and an oxygen content of 1.80% is prepared by taking fluorinated carbon with a fluorine content of 55.97% as a raw material as an example, and the effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified by specific experiments, as follows:
[0050] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0051] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.2 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.2, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0052] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of the reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 200 degrees Celsius for 6 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0053] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0054] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0055] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0056] Embodiment 4
[0057] In this embodiment, carbon fluoride with a fluorine content of 55.97% is used as a raw material to prepare a modified fluorinated graphite nanosheet with a fluorine content of 45.62% and an oxygen content of 2.68%. The effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified through specific experiments, as follows:
[0058] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0059] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.8 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.8, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0060] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of the reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 200 degrees Celsius for 6 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0061] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0062] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0063] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0064] Embodiment 5
[0065] In this embodiment, carbon fluoride with a fluorine content of 55.97% is used as a raw material to prepare a modified fluorinated graphite nanosheet with a fluorine content of 53.00% and an oxygen content of 0.90%. The effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified through specific experiments, as follows:
[0066] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0067] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.5 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.5, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0068] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of a reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 100 degrees Celsius for 6 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0069] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0070] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0071] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0072] Embodiment 6
[0073] In this embodiment, carbon fluoride with a fluorine content of 55.97% is used as a raw material to prepare a modified fluorinated graphite nanosheet with a fluorine content of 46.00% and an oxygen content of 2.55%. The effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified through specific experiments, as follows:
[0074] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0075] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.5 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.5, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0076] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of a reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 300 degrees Celsius for 6 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0077] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0078] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0079] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0080] Embodiment 7
[0081] In this embodiment, a modified fluorinated graphite nanosheet with a fluorine content of 49.00% and an oxygen content of 1.70% is prepared by taking fluorinated carbon with a fluorine content of 55.97% as a raw material as an example, and the effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified by specific experiments, as follows:
[0082] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0083] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.5 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.5, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0084] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of a reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 200 degrees Celsius for 4 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0085] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0086] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0087] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0088] Embodiment 8
[0089] In this embodiment, a modified fluorinated graphite nanosheet with a fluorine content of 45.00% and an oxygen content of 2.80% is prepared by taking fluorinated carbon with a fluorine content of 55.97% as a raw material as an example, and the effect of the preparation method provided in this embodiment on the fluorine content of the modified fluorinated graphite nanosheet is verified by specific experiments, as follows:
[0090] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0091] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.5 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.5, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0092] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of a reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 200 degrees Celsius for 8 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0093] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0094] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0095] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0096] Comparative Example 1
[0097] Compared with Example 1, in this comparative example, oxalic acid was not added, and other reaction conditions were the same. The fluorine content of the obtained fluorinated carbon was 55.97%, and the oxygen doping amount was 0.69%, as follows:
[0098] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0099] (2) adding 60 ml of deionized water to the dispersed carbon fluoride solution without adding oxalic acid, ultrasonicating the mixed solution for 10 minutes and then stirring the solution for 30 minutes to fully disperse and mix uniformly;
[0100] (3) transferring the above-mentioned fully dispersed mixed solution into the inner container of the reaction kettle, and then placing the inner container into the reaction kettle for hydrothermal reaction at 200 degrees Celsius for 6 hours;
[0101] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent washing is placed in a cold trap for 6 hours and then freeze-dried for 16 hours to obtain unmodified fluorinated carbon;
[0102] (5) The carbon fluoride-modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with a conductive agent, a binder, etc., an electrode is obtained, and metallic lithium is used as a negative electrode to assemble a lithium / carbon fluoride battery.
[0103] The carbon fluoride prepared in this embodiment is used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing carbon fluoride, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring to form a gel; mixing the carbon fluoride and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then coating the slurry on a carbon-coated aluminum foil with a thickness of 100 microns, and vacuum drying for 24 hours to obtain an electrode; the counter electrode is metallic lithium, the diaphragm is a Celgard-2500 series polypropylene diaphragm, and the electrolyte is 1M LiBF4 / PC:DME (1:1); 2025 button cells were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell - lithium sheet - electrolyte - diaphragm - electrolyte - electrode sheet - gasket - spring sheet - positive electrode shell. After assembly, it was packaged and finally tested for its performance.
[0104] Comparative Example 2
[0105] Compared with Example 4, in this comparative example, the reaction temperature was changed to 100 degrees Celsius, the reaction time was 8 hours, and the fluorine content of the obtained modified fluorinated graphite nanosheets was 52.00%, and the oxygen doping amount was 1.20%, as follows:
[0106] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0107] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 1.8 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:1.8, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0108] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of a reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 100 degrees Celsius for 8 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0109] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0110] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0111] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0112] Comparative Example 3
[0113] In this comparative example, compared with Example 8, the ratio of carbon fluoride to defluorinating agent was increased to 1:3, the reaction time was 6 hours, and the fluorine content of the obtained modified fluorinated graphite nanosheets was 35.00%, and the oxygen doping amount was 3.50%, as follows:
[0114] (1) Disperse 1 g of carbon fluoride in 10 ml of anhydrous ethanol solution, stir for 10 minutes at 800 rpm, and then sonicate for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution;
[0115] (2) Add 60 ml of deionized water to the dispersed carbon fluoride solution, and then add 3.0 g of oxalic acid, where the mass ratio of the added carbon fluoride to the oxalic acid is 1:3.0, stir for 10 minutes to fully dissolve the oxalic acid, then sonicate for 10 minutes and stir for 30 minutes to make it evenly dispersed;
[0116] (3) transferring the above-mentioned fully dispersed mixed solution into the inner tank of the reactor, and then placing the inner tank into the reactor for hydrothermal reaction at 200 degrees Celsius for 6 hours. During the hydrothermal reaction, oxalic acid is thermally decomposed to produce carbon dioxide, carbon monoxide and water. Carbon monoxide has a strong reducing property and can cause carbon fluoride to undergo a reduction defluorination reaction;
[0117] (4) After the reactor is cooled to room temperature, the product is filtered and washed three times with deionized water and anhydrous ethanol alternately, and the sample after the residual solvent is washed is placed in a cold trap and frozen for 6 hours, and then freeze-dried for 16 hours to obtain modified fluorinated graphite nanosheets;
[0118] (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with conductive agents, binders, etc., electrodes are obtained, and metallic lithium is used as negative electrode to assemble into lithium / carbon fluoride batteries.
[0119] The modified fluorinated graphite nanosheets prepared in this embodiment are used as the positive electrode active material to prepare a lithium / carbon fluoride button battery. The specific method includes: weighing the modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride in a ratio of 8:1:1; placing the polyvinylidene fluoride in a small beaker, adding a certain amount of N-methylpyrrolidone and stirring it into a gel; mixing the modified fluorinated graphite nanosheets and the conductive Ketjen black evenly, and then slowly adding them to the beaker; adding an appropriate amount of N-methylpyrrolidone until a uniformly dispersed slurry is obtained, and then It was coated on carbon-coated aluminum foil with a thickness of 100 microns and vacuum dried for 24 hours to obtain an electrode. The counter electrode was metallic lithium, the diaphragm was a Celgard-2500 series polypropylene diaphragm, and the electrolyte was 1MLiBF4 / PC:DME (1:1). 2025 button batteries were used for assembly. The whole process was carried out in a glove box. The assembly sequence was negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-positive electrode shell. After assembly, it was packaged and finally its performance was tested.
[0120] Table 3 is a table showing the relative contents of C, F, and O elements in carbon fluoride and modified fluorinated graphite nanosheets and the ratio of F / C provided in one embodiment of the present invention;
[0121] Table 4 is a relative content table of CF, C-F2, SiC-F, C=O, CO, and C=C obtained by peak fitting in the C1s spectra of carbon fluoride and modified fluorinated graphite nanosheets provided in one embodiment of the present invention;
[0122]
[0123] Table 1
[0124]
[0125] Table 2
[0126] sample C (at%) F(at%) O(at%) F / C Before modification 43.34 55.97 0.69 1.29 After modification 51.28 46.43 2.28 0.90
[0127] Table 3
[0128]
[0129] Table 4
[0130] In summary, compared with the poor conductivity and unsatisfactory rate performance of existing fluorinated carbon, the present invention provides a method and battery for preparing modified fluorinated graphite nanosheets in one step by a liquid phase exfoliation method, wherein the fluorinated carbon is dispersed in an anhydrous ethanol solution, and then deionized water and a defluorinating agent are added to form a mixed solution, and the mixed solution dissolved with the defluorinating agent is hydrothermally reacted at 100 to 300 degrees Celsius for 4 to 8 hours, and the modified fluorinated graphite nanosheet is obtained after freeze drying. Among them, due to the different masses of the added defluorinating agent, the modified fluorinated graphite nanosheet has different fluorine contents (31% to 54%) and different oxygen doping amounts (0.69% to 3.50%). The fluorine content of the material is reduced by the defluorinating agent, and the defects generated by the defluorination process are used to make it easier for oxygen to be incorporated into the material, thereby achieving synchronous oxygen doping, and simultaneously achieving the transformation from fluorinated carbon to modified fluorinated graphite nanosheets. As shown in Example 1, under the conditions of a mass ratio of carbon fluoride to oxalic acid of 1:1.5, a hydrothermal reaction temperature of 200 degrees Celsius, and a reaction time of 6 hours, the prepared modified fluorinated graphite nanosheets have a fluorine content of 48.41% and an oxygen doping amount of 2.28%. The lithium / carbon fluoride battery assembled with electrodes prepared with a ratio of modified fluorinated graphite nanosheets, Ketjen black, and polyvinylidene fluoride of 8:1:1 has a maximum discharge rate of 45C, and its specific capacity is still 366.76 mAh g at the maximum discharge rate. -1 . The modified fluorinated graphite nanosheets prepared under other reaction conditions have reduced fluorine content, increased oxygen content, and significantly improved rate performance compared to the original material. In summary, it is shown that the prepared modified fluorinated graphite nanosheets not only improve the electrical conductivity, but also ensure the high specific capacity of the lithium / carbon fluoride battery and increase the platform voltage of the lithium / carbon fluoride battery at high rate discharge, significantly improving the electrochemical performance of the lithium / carbon fluoride battery.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement and improvement made within the spirit and scope of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing modified fluorinated graphite nanosheets in one step by liquid phase exfoliation and a battery, characterized in that: The method comprises: The carbon fluoride is immersed in a mixed solution of deionized water and anhydrous ethanol, a defluorinating agent is added and then a hydrothermal reaction is carried out, and the product obtained by the hydrothermal reaction is repeatedly washed with alcohol and water alternately and then freeze-dried to obtain a modified fluorinated graphite nanosheet, wherein the modified fluorinated graphite nanosheet has a fluorine content of 31% to 54% and an oxygen doping amount of 0.69% to 3.50%.
2. The method for preparing modified fluorinated graphite nanosheets according to claim 1, characterized in that: The method further comprises: (1) dispersing carbon fluoride in an anhydrous ethanol solution, stirring for 10 minutes and then ultrasonicating for 10 minutes to fully disperse the carbon fluoride in the anhydrous ethanol solution; (2) adding deionized water and a defluorinating agent to the dispersed carbon fluoride solution, wherein the mass ratio of carbon fluoride to the defluorinating agent is 1:(0.5-3.0), stirring for 10 minutes to fully dissolve the defluorinating agent, ultrasonicating for 10 minutes, and stirring for 30 minutes to make it evenly dispersed; (3) subjecting the above-mentioned fully dispersed mixed solution to a hydrothermal reaction at 100 to 300 degrees Celsius for 4 to 8 hours, during which the defluorinating agent is thermally decomposed to produce carbon dioxide, carbon monoxide and water, wherein carbon monoxide has a strong reducing property and can cause the carbon fluoride to undergo a reduction defluorination reaction; (4) washing the product of the hydrothermal reaction with deionized water and anhydrous ethanol alternately and repeatedly by suction filtration three times, and freeze-drying the sample after washing the residual solvent to obtain modified fluorinated graphite nanosheets; (5) The modified fluorinated graphite nanosheets are used as positive electrode active materials, and after slurry mixing, coating, drying, cutting and other processes with a conductive agent, a binder, etc., an electrode is obtained for assembling a lithium / carbon fluoride battery.
3. The method for preparing modified fluorinated graphite nanosheets according to claim 2, characterized in that: The fluorine content of the carbon fluoride is 50-70%, and the oxygen content is 0-0.69%.
4. The method for preparing modified fluorinated graphite nanosheets according to claim 2, characterized in that: The defluorination agent includes at least one of oxalic acid, sodium bicarbonate and carbon monoxide, and the oxygen source includes at least one of oxalic acid and sodium bicarbonate.
5. The method for preparing modified fluorinated graphite nanosheets according to claim 2, characterized in that: During the hydrothermal reaction, oxalic acid is decomposed by heat to produce carbon dioxide, carbon monoxide and water, wherein the generated carbon dioxide enters the gaps between the layered carbon fluoride layers and converts them into flaky graphite fluoride nanosheets. The generated carbon monoxide has strong reducing properties and can undergo a reduction reaction with fluorine in the carbon fluoride to achieve defluorination, generating carbon dioxide and hydrogen fluoride. The fluorine content of the carbon fluoride is significantly reduced after the reductive defluorination, and oxygen is doped into the carbon fluoride during the reaction.
6. The method for preparing modified fluorinated graphite nanosheets according to claim 2, characterized in that: The slurry adjustment ratio is a mass ratio of modified fluorinated graphite nanosheets: conductive agent: binder, including at least one of 8:1:1, 0.82:0.09:0.09 and 0.86:0.07:0.
07.
7. The method for preparing modified fluorinated graphite nanosheets according to claim 2, characterized in that: The conductive agent includes at least one of Ketjen black, Super P, carbon nanotubes and carbon fibers.
8. The method for preparing modified fluorinated graphite nanosheets according to claim 2, characterized in that: The binder is at least one of polytetrafluoroethylene and polyvinylidene fluoride.
9. The method for preparing modified fluorinated graphite nanosheets according to claim 2, characterized in that: The slurry preparation solvent is N-methylpyrrolidone. The modified fluorinated graphite nanosheets, the conductive agent, and the binder are made into a slurry, which is coated on a carbon-coated aluminum foil, and then cut into pieces after drying to prepare electrodes.
10. A battery, characterized in that: The modified fluorinated graphite nanosheet is prepared by the method for preparing the modified fluorinated graphite nanosheet according to claims 1-9.